Prevalence of underweight, overweight and obesity in preschool children of Tehran, Iran - Abbasali Gaeini; Majid Kashef; Ali Samadi; Aliasghar Fallahi (Journal of Research in Medical Sciences, 2011)
Background: It is reported that prevalence of overweight and obesity have increased in all age groups, but little is known about prevalence of overweight and obesity in preschool children. Therefore, the purpose of this study was to survey the prevalence of underweight, overweight and obesity in 3-6 year-old Tehranian children in 2009-2010. Methods: This cross-sectional study was performed on a total of 756 (378 boys and 378 girls) preschool children aged 3-6. Subjects were selected through stratified sampling from 5 geographic regions of Tehran (east, west, north, south, and center). Body weight and height were measured directly. Underweight, overweight and obesity was defined as Body Mass Index (BMI) ≤ 5 th percentile (underweight), 5 th to 85 th percentile (normal weight), 85 th to 95 th percentile (overweight), and > 95 th percentile (obesity); based on recommendation of Centers for Disease Control (CDC) in 2000. Results: Findings showed that the prevalence of underweight, overweight and obesity was 4.77%, 9.81% and 4.77% in boys and 4.77%, 10.31% and 4.49% in girls, respectively. Conclusions: Our findings showed a relatively high prevalence of overweight and obesity in Tehranian preschool children that is a serious problem. This result can be used in clinical setting and preventive programs.